Integrating Hifz al-Bi'ah into Industrial Governance: A Sharia and Al-Maslahah Maqashid Based Framework for the Circular Economy - Muhamad Fikri Ramadan; Falah Alkautsar; Ade Apriyani; Mohammad Ridwan (Ecobankers : Journal of Economy and Banking, 2026)
Governance require radical change. From a different perspective, Islamic principles such as maqasid sharia (the principles of Islamic law) and al-maslahah (the principles of social responsibility) can be used to combine environmental preservation (hifz al-bi'ah) with modern industrial governance within a circular economy framework. A systematic literature review shows that Islamic legal principles have established the ethical and normative foundations for sustainable industrial practices. This research method uses a descriptive qualitative method with a literature review. The results show that hifz al-bi'ah is a crucial part of al-dharuriyyat al-khamsah and constitutes a comprehensive plan for adopting a circular economy. In the context of the transition to a circular economy, the principles of istikhlaf, tawazun, and mas'uliyyah—namely, stewardship, ecological balance, and accountability—become more evident. From an Islamic economic perspective, this paper proposes a framework that combines traditional Islamic jurisprudence with today's pressing sustainability needs and can be a significant contribution to the ongoing discourse on Islamic economics